#TITLE_ALTERNATIVE# - Rustiani (NIM:250 93 011), Siska
Abstract: Understanding soil behaviour and mobilizing for an accurate analyse and design geotechnical engineering is very important.An efficient solution method to analyze the problem is necessary as well to obtain an optimum design.The deformations and stresses that in the soil caused by open braced excavation is the main problem studied in this thesis. Finite element method using Soil-Struct (Duncan & Clough,1990) package was used in the analysis. The program employs hyperbolic soil and interface stress strain relations. Both undrained and drained condition were considered in the analysis. Result of finite element analysis were compared to the conventional Terzaghi & Peck method and instrumented observation in the field. Spesific analysis were performed for excavation soil of : Coke Pit in St.Lousiana,Wmata Subway station in Anacostia area of Washington DC,and Tambak Lorok Semarang.Result of the analysis indicated that Soil-Struct program is useful in analysing braced cut excavation, especially for comprehensive stresses and deformations that affect the general stability. The study shows that finite element resuls predict field observation fairly well for undrained condition . In addition, it is found that for undrained conventional method overpredict strut loads,and lateral pressure compared to the finite element results.Another finding is that vertical deformation at base of the excavation (heave) for drained condition always larger than that of undrained condition.